REPRESENTASI AHOK DALAM KASUS PENISTAAN AGAMA PADA SURAT KABAR BERDASARKAN ANALISIS SEMIOTIKA ROLAND BARTHES - I Gusti Ayu Rai; Adi Bayu Mahadian (Dialektika, 2017)
Jakarta governor candidate, known as Ahok tangled case of blasphemy, offensive surah Al-Maidah 51 during his campaign in the thousand islands. The case became a highlight public concern, especially among the Muslim community fatherly who considered him one insults the Islamic religion. These blasphemy cases reported by the mass media in Indonesia, some mass media reported Ahok case with the cartoon is the newspaper Suara Merdeka and Rakyat Merdeka. This study aims to determine the semiotic meaning of "Representation Ahok In Case of Defamation of Religion On Newspaper (Roland Barthes Semotika Analysis On Cartoon Ahok In Newspapers Suara Merdeka, Rakyat Merdeka period October-December 2016)" which analyzes the meaning of denotation, connotation and myth according to Roland Barthes seen from Expression Symbols, Gestures, Property, typography and color. The theory is to use Roland Barthes Semiotics Analysis of the significance of the stage. The method used in this research is qualitative with constructivist paradigm.From the results of research conducted through the stages of Roland Barthes meaning that denotative, connotative, and the myth of the newspapers Suara Merdeka and Rakyat Merdeka, representation Ahok cartoons in newspapers. Ahok is the figure of the minorities who do not have the authority and power in the majority of the political elite, especially in Indonesia. Ahok feel threatened by the charges of blasphemy against him, and charged with blasphemy is politicized by some politicians who oppose Ahok.